Transplantation of Gut Microbiota From High-Fat-Diet-Tolerant Cynomolgus Monkeys Alleviates Hyperlipidemia and Hepatic Steatosis in Rats - Gao, Jiang-Mei; Rao, Jun-Hua; Wei, Zhi-Yuan; Xia, Shou-Yue; Huang, Li; Tang, Ming-Tian; Hide, Geoff; Zheng, Ting-Ting; Li, Jia-Huan; Zhao, Guo-An; Sun, Yun-Xiao; Chen, Jian-Huan (Frontiers in Microbiology, 2022)
Emerging evidence has been reported to support the involvement of the gut microbiota in the host’s blood lipids and hyperlipidemia (HLP). However, there remains unexplained variation in the host’s blood lipids phenotype. Here in a nonhuman primate HLP model was established in cynomolgus monkeys fed a high-fat diet (HFD) for 19 months. At Month 19, 60% (3/5) of the HFD monkeys developed HLP, but surprisingly 40% of them (2/5) exhibited strong tolerance to the HFD (HFD-T) with their blood lipids profiles returning to normal levels. Metagenomic analysis was used to investigate the compositional changes in the gut microbiota in these monkeys. Furthermore, the relative abundance of Megasphaera remarkably increased and became the dominant gut microbe in HFD-T monkeys. A verification experiment showed that transplantation of fecal microbiota from HFD-T monkeys alleviated reduced the blood lipids levels and hepatocyte lesion in HLP rats. Furthermore, the relative abundance of Megasphaera significantly increased in rats receiving transplantation, confirming the successful colonization of the microbes in the host and its correlation with the change of the host’s blood profiles. Therefore, our results thus suggested a potentially pivotal lipid-lowering role of Megasphaera in the gut microbiota, which could contribute to variation in the host’s blood lipid